Pengaruh Keterlibatan Karyawan dan Pengembangan Karir terhadap Retensi Karyawan pada PT Chalodo Sibali Resoe - Annisa Sabella; Altri Wahida; Saharuddin Saharuddin (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The purpose of this study is to determine the effect of employee engagement and career development on employee retention at PT Chalodo Sibali Resoe. This study uses a quantitative approach, and the data is in numerical form. The research design uses a questionnaire. The population and sample in this study are all 33 employees. The sample was determined using a saturated sampling method. The data obtained were analyzed using multiple linear regression. The results of the analysis show evidence that simultaneously, employee engagement and career development have a positive and significant effect on employee retention with a calculated f value of 132.103 > 3.32 (f table) and a significance value of <0.001 < 0.05. This indicates that improvements in appreciation, recognition, and harmonious working relationships at PT Chalodo Sibali Resoe will be effective in retaining employees. Employee engagement with structured career development programs is not only an investment in capability improvement but also an effective strategy for retaining key talent at PT Chalodo Sibali Resoe in North Luwu. This study provides practical implications for company management in designing employee engagement and career development strategies to improve employee retention.